Effect of Buttermilk on the Physicochemical, Rheological, and Sensory Qualities of Pan and Pita Bread - Amani H. Al-Jahani (International Journal of Food Science)
The aim of this study was to evaluate the influence of buttermilk on the physicochemical and sensory attributes of pan and pita breads. Different amounts of buttermilk (30, 60, and 100% of added water) were mixed with other ingredients of pan and pita bread formulations. The doughs and bread were analyzed for rheological, physicochemical, and sensory qualities. The results demonstrated that incorporation of different concentrations of buttermilk in bread formulations progressively enhanced water absorption capacity, dough development time, gelatinization temperature, and peak viscosity, whereas it reduced the dough stability and temperature at peak viscosity. Supplementation of wheat flour with 30% buttermilk significantly (P ≤ 0.05) enhanced the physical properties of pan bread compared to nonsupplemented control. Incorporation of different percentages of buttermilk in bread formulation concomitantly (P ≤ 0.05) increased protein, oil, and ash contents and it reduced the carbohydrate contents of both types of bread. Incorporation of 60 and 100% of buttermilk in bread formula showed low scores of all sensory attributes compared to control and 30% buttermilk containing pan and pita bread. In conclusion, supplementation of bread formulas with 30% buttermilk is recommended for improving the nutritional and sensorial qualities of pan and pita bread.